Chemo-mechanical processing of hot chamber die cast scrap to design ZnO-based composite anode for lithium-ion batteries - Karahan, Billur Deniz; Gülcan, Mehmet Feryat (Elsevier Ltd, 2024)
Zn–4Al alloy is mostly processed via high pressure, hot chamber die-casting method. For the first time in the open literature, in this study a novel and useful advice regarding the valorization of zinc die-cast scrap in green energy applications is realized. Herein, firstly a chemo-mechanical process is utilized to form ZnO rich powder (sample 1), then ball milling of this powder with carbon is accomplished to fabricate composite powder (sample 2). Unlike synthetic ZnO, the galvanostatic test demonstrates that the composite electrode (Sample 2) delivers 661.7 mA h/g capacities at 100th cycle when tested under a current load of 50 mA/g and performs 441.7 mA h/g capacities after 500 cycles, when 0.1 A/g current load is applied. Such performance can be related to the particularities in the morphology, the structure, and the chemistry of the designed composite powder.
Keywords: Ball Milling; Chemo-Mechanical Processing; Green Electrode; Waste to Wealth; Waste Valorization; ZnO-Based Composite